Social business in multinational corporations: an analysis of marketing practices - Chaves, Thiago José de; Rocha, Thelma; Reuther, Jana; Galhanone, Renata Fernandes (Internext, 2017)
Social business (SB) as a category of organization that seeks to create long-term economic and social value for the majority of the people has attracted the attention of policy-makers, practitioners, and scholars. Some authors highlight the role that multinational corporations (MNCs) have in mitigating social and environmental problems by offering products and services to meet the demands of lower-income populations. Based on a discussion of social business and such initiatives inside MNCs, this article investigates how the Brazilian subsidiaries of two large MNCs (Coca-Cola and Danone) are performing SB in a developing country. More specifically, we focused on how they are using their marketing know-how to achieve the desired results. The cases were chosen based on their global relevance, reach, and representativeness in SB efforts. Our study has shown that their social initiatives are linked to the corporate mission, values and strategies, and that they aim to achieve social transformation in connection to their core business. Our goal is to contribute both to academic research and to future initiatives in Brazil and other developing countries.